Estudios genéticos sobre espina bífida en Chile ¿Por dónde comenzar? - Pardo V., Rosa; Suazo S., José Lorenzo; Castillo T., Silvia (Revista Hospital Clínico Universidad de Chile, 2011)
Neural tube defects (NTDs) are a group of congenital anomalies that affect the central nervious system. Spina Bifida (SB) is the most frecuent NTD in live births andi t is usually associated to disease, disability; and mortality. NTDs are considered as a multifactorial disease. Women who use folic acid periconceptionally are at a 50-70% reduced risk for NTD-affected pregnancies. More than 80 candidates genes to SB are been studied, someones related to folic acid metabolic pathway. MTHFR gene is the gene more studied in NTDs. Its allele 677T is asóciate to higher risk to NTD. It is important to study polymorphisms in MTHFR gene in Chile because Chilean population has dfferent ethnic origen from others previous studied populations.